Statistical Evaluation of Non-Agglomerating Coating for Granulated Natural Asphalt - Tjokorde Walmiki Samadhi; I Dewa Gede Arsa Putrawan; Bambang Eko Prabowo; Alinda Dwitawidi (Journal of Engineering and Technological Sciences, 2011)
Agglomeration of granulated Buton natural asphalt during storage is of major concern in its large-scale commercial application. This work develops a simple test method to evaluate the performance of agglomeration-resistant coating for granulated Buton asphalt, consisting of water-based polymeric primary coating and mineral-based secondary coating. The method uses a static load cell to measure the agglomerated granule count fraction under simulated storage conditions. A 24-1 fractional factorial experiment with two replications is employed to evaluate the effect of coating drying temperature, drying time, asphalt to secondary coating mass ratio, and secondary coating type on the agglomerated count fraction at ambient temperature and 60 oC. The test is able to measure a statistically significant increase in agglomeration resistance when the coating is applied, with an agglomerated fraction of 17.5% at 60 oC. The test identifies asphalt to secondary coating weight ratio as a significant factor, with an ANOVA p-value much lower than other effects. A decrease in this mass ratio from 5:1 to 5:2 increases the agglomeration, which is hypothesized to be attributed to the hydrated cementitious phase between granular external surfaces. More work is needed to identify the acceptable fraction of agglomerated granules.